Analisa Performansi Jaringan Telekomunikasi Fiber to the Home (FTTH) Menggunakan Metode Power Link Budget Pada Kluster Bhumi Nirwana Balikpapan Utara - Amalia Rizqi Utami; Della Rahmayanti; Zafira Azyati (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Currently, the technology needed in the era of digitalization is increasing rapidly. Especially, the need of an internet network. During this pandemic, which requires people to carry out their activities from home or known as Work From Home (WFH). In order to support the success of WFH activities, an adequate internet connection is required. Based on these problems, this study was conducted to analyze the performance of the Fiber to the Home (FTTH) telecommunications network in the Bhumi Nirwana Cluster, Batu Ampar, North Balikpapan. The analysis technique chosen designed a simulation using OptiSystem software and mathematical calculations using the Power Link Budget method. After a sessions of experiments and mathematical calculations, it can be concluded that the Bit Error Rate (BER) value obtained is categorized as "Fair" based on the BER value indicator which does not exceed 10e-9 which is the standard value. In mathematical calculations used the Power Link Budget method, on the uplink and downlink sides, the average value of the total attenuation is obtained with "good" results, which is less than 28 dB and has met the ITU-T G.984 standard, the value of the average the average maximum power sensitivity is greater than -28 dBm and the value of the average power margin is more than 0 dB which indicates the results of these two values have accepted the standard.